2012
DOI: 10.5194/hess-16-4483-2012
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the physical controls of regional patterns of flow duration curves – Part 4: A synthesis of empirical analysis, process modeling and catchment classification

Abstract: Abstract. The paper reports on a four-pronged study of the physical controls on regional patterns of the flow duration curve (FDC). This involved a comparative analysis of longterm continuous data from nearly 200 catchments around the US, encompassing a wide range of climates, geology, and ecology. The analysis was done from three different perspectives -statistical analysis, process-based modeling, and databased classification -followed by a synthesis, which is the focus of this paper. Streamflow data were se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 33 publications
5
46
0
Order By: Relevance
“…This is in line with studies stating that each FDC segment can be related to certain catchment processes (Yilmaz et al, 2008;Yaeger et al, 2012;Pfannerstill et al, 2015). The strong connective strength of model parameters regulating water balance to mid-flows as well as of parameters from slow reacting aquifer storages to very low flows is derived in this study.…”
Section: Benefit Of Using Different Performance Criteriasupporting
confidence: 67%
See 2 more Smart Citations
“…This is in line with studies stating that each FDC segment can be related to certain catchment processes (Yilmaz et al, 2008;Yaeger et al, 2012;Pfannerstill et al, 2015). The strong connective strength of model parameters regulating water balance to mid-flows as well as of parameters from slow reacting aquifer storages to very low flows is derived in this study.…”
Section: Benefit Of Using Different Performance Criteriasupporting
confidence: 67%
“…FDC signatures consider that different discharge magnitudes are controlled by different processes. Whilst the high-flow segment is mainly impacted by precipitation and fast runoff components, low flows are controlled by evapotranspiration and deep groundwater storages (Yilmaz et al, 2008;Cheng et al, 2012;Pokhrel et al, 2012;Yaeger et al, 2012;Guse et al, 2016) For the evaluation of each FDC segment, the RSR, the ratio of the root mean square error to the standard deviation, was calculated for each FDC segment (Eq. 3) (Moriasi et al, 2007), which allows fair comparison between different segments (Haas et al, 2016).…”
Section: Performance Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…This structure has been investigated through the prism of signatures including the flood frequency curve (e.g., Robinson and Sivapalan, 1997), water balance partitioning Harman et al, 2011;Sivapalan et al, 2011a), flow duration curve Yaeger et al, 2012;Ye et al, 2012), recession curve (e.g., Wittenberg, 2003), preferred states in the soil moisture distribution (e.g., Western and Grayson, 2001), and seasonal variations in the fluxes measured at an eddy-flux tower . The study of regimes adopts the Darwinian approach of analyzing populations but in the temporal domain (understanding a population of events within a watershed).…”
Section: Variation Across Time: Regimes and Filteringmentioning
confidence: 99%
“…It is well documented that hydro-climatological processes within a catchment are reflected in the FDC (e.g. Cheng et al, 2012;Ye et al, 2012;Coopersmith et al, 2012;Yaeger et al, 2012;Botter et al, 2008), and therefore the model parameters identified solely by a regional FDC are expected to provide reliable predictions in ungauged catchments (e.g. Westerberg et al, 2014;Yu and Yang, 2000).…”
Section: Rfdc_cal For Rainfall-runoff Modelling In Ungauged Catchmentsmentioning
confidence: 99%